Bahasa Inggris - Novi Yanti; Nurtati Nurtati (Jurnal Pembangunan Nagari, 2020)
The allocation of development budget can accelerate the pace of economic growth in the implementation of fiscal decentralization. Through locally-generated revenue management and regional government, balance funds can increase their income through the use of appropriate capital expenditure however economic growth is not always linear with all sources of revenue. The purpose of this study is to analyze the effect of regional revenue and balance funds partially and simultaneously on capital expenditure and its impact on economic growth. The research method is quantitative with a longitudinal research time-series design. The study was conducted in the Regency / City of West Sumatra Province with secondary data from the Central Statistics Agency in 2009-2018. Research analysis using multiple linear regression test and path analysis. The results showed that Locally-generated revenue, general, and special allocation fund partially and simultaneously have a significant effect on capital expenditure, but the profit-sharing fund partially has no significant effect on capital expenditure. Locally-generated revenue, profit-sharing funds, general and special allocation fund, and capital expenditure partially and simultaneously have a significant effect on economic growth. Likewise, capital expenditure has a positive effect on economic growth which is mediated by locally-generated revenue and special allocation funds, while capital expenditure does not significantly influence economic growth mediated by general allocation funds and profit-sharing funds